CRICKET POWDER (ACHETA DOMESTICA) AS FOOD ADDITIVE FOR PROCESSING OF DRY-FERMENTED POULTRY BARS - DESISLAVA B. VLAHOVA-VANGELOVA; DESISLAV K. BALEV; NIKOLAY D. KOLEV; DILYANA N. GRADINARSKA; STEFAN G. DRAGOEV (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In the recent years crickets, as well as cricket powder (CP) are interesting food ingredients in the European market. Some benefits of CP are high content of quality proteins, fats, vitamins and minerals and little environmental footprint. The aim of this work was to explore the impact of CP additive (2 and 4 %) on the color characteristics, technological and sensory properties of dry-fermented poultry bars. The use of CP as meat additive significantly decreases L* and a* values of the product. Structural strength, plastic strength and pH were significantly increased (p ˂ 0.05) in CP enriched raw and dry-fermented poultry bars. The moisture content and water activity (aw) in the final CP enriched poultry products increased (p ˂ 0.05). The incorporation of 2 % CP had slight impact on sensory properties of final product and can be successfully used for processing of value-added meat products. CP addition up to 4 % had negative effect on the color, sensory properties, structural and plastic strength on the filling mass and dry-fermented meat bars.